Perubahan warna semen ionomer kaca setelah direndam dalam larutan teh hitam - Wahyu Puri Wardhani; Asti Meizarini; Anita Yuliati; Retna Apsari (DiscoverSys Inc., 2010)
Microporosity in glass ionomer cement contributes on its colour stability. In oralcavity GIC interacts with saliva, foods, drinks, and the oral hygiene condition whichcould affect in colour stability. This study aimed to examine the colour change in GICafter immersion in black tea solution. Twenty eight disc specimens (6 mm diameterand 1 mm thickness). The colour measurements were recorded after storage in closedtube for 24 hours. Specimens were randomly devided into 4 groups of 7 specimens.Control specimens were kept in saline solution. The other 3 groups were immersed inblack tea solution for 5 minutes respectively for 5, 7, and 14 times, followed by colourchange measurement. Data were submitted to one-way ANOVA and LSD. There wassignificant colour change in GIC after immersion in black tea. The conclusion islonger GIC immersed in black tea lower the intensity. The lowest intensity changingwas the immersed for 5 minutes, 14 times daily.